Screening for Symptoms of Postpartum Traumatic Stress in a Sample of Mothers with Preterm Infants. (1st March 2014) - Shaw, Richard J.; Lilo, Emily A.; Storfer-Isser, Amy; Ball, M. Bethany; Proud, Melinda S.; Vierhaus, Nancy S.; Huntsberry, Audrey; Mitchell, Kelley; Adams, Marian M.; Horwitz, Sarah M.
<x xml:space="preserve">Abstract</x> There are no established screening criteria to help identify mothers of premature infants who are at risk for symptoms of emotional distress. The current study, using data obtained from recruitment and screening in preparation for a randomized controlled trial, aimed to identify potential risk factors associated with symptoms of depression, anxiety and posttraumatic stress in a sample of mothers with premature infants hospitalized in a neonatal intensive care unit. One hundred, thirty-five mothers of preterm infants born at 26–34 weeks of gestation completed three self-report measures: the Stanford Acute Stress Reaction Questionnaire, the Beck Depression Inventory (2nd ed.), and the Beck Anxiety Inventory to determine their eligibility for inclusion in a treatment intervention study based on clinical cut-off scores for each measure. Maternal sociodemographic measures, including race, ethnicity, age, maternal pregnancy history, and measures of infant medical severity were not helpful in differentiating mothers who screened positive on one or more of the measures from those who screened negative. Programs to screen parents of premature infants for the presence of symptoms of posttraumatic stress, anxiety, and depression will need to adopt universal screening rather than profiling of potential high risk parents based on their sociodemographic characteristics or measures of their infant's medical severity.